Workers housing, the built and unbuilt morphologies: A case study from the Lisbon Region, Portugal - Marat-Mendes, T.; Fernandes del Pino, R.; Borges, J.C. (19th International Planning History Society Conference. City Space Transformation, 2022)
This study focuses on the housing estate for the workers of the Sacor oil refinery in Bobadela, a town of the Lisbon Region, planned in 1956-62. Its context is one of political, social and economic changes which transformed the Lisbon Region, with greater implications on its industrial fabric and its supporting residential areas which have continued to evolve. We purpose the reding of sustainability through three information layers: urban process, examination of planning instruments and morphological analysis. Urban process designates the social, political and institutional conditions determining urban form, including through planning and design. In Portugal, across different paradigms, planning instruments stand on the opposition between urban and rural land. However, the importance of local food- production, of mixed land-uses and a balance between household activities and labour are now acknowledged as critical factors for urban sustainability. Apparently, the 1960s plan for the Sacor Estate materialized such concerns. We depict the specificity of such concerns for both the built elements as well as the unbuilt ones, thorough a morphological analysis and identifying building/green space typologies. From the design to the urban process, the Sacor housing estate may provide lessons for the present and the future, promoting personal well- being and for sustainability.